K etno-nacionalni identiteti koroških in tržaških Slovencev - Jurić-Pahor, Marija (Annales. Series historia et sociologia, 1998)
The article focuses on the presentation of historically conditioned "inner systematics" of ethno-national identity, which is linked to the cultural matrix (Gr. mater arché, Lat. natio) and has experienced, with the affirmation of the father (Gr. pater arché, Lat. patria), a radical break. Attention to it is drawn by the term "the nation's rebirth", which presupposes a negation of the birth from woman and a rebirth from man. In Oresteia, the god Apollo says: "It is not the mother who conceives a child, she only nurses him with care. It is the father who conceives, while the mother looks after the stock. "The aim of this formula, which is immanent to all rituals of initiation and rebirth, is to loosen the ties between boys and their mothers and to attract novices to the company of men ...
Keywords: Carinthian Slovenes; koroški Slovenci; nacionalna identiteta; narodne manjšine; tržaški Slovenci; zamejski Slovenci